Effect of Interface Layer Capacitance on Polydimethylsiloxane in Electrowetting-on-Dielectric Actuation. (6th January 2015) - Sohail, Shiraz; Das, Soumen; Biswas, Karabi
Abstract : Electrowetting is an effective way to manipulate small volume of liquid in microfluidic applications. It has been sophisticatedly used in the fields of Lab-on-a-Chip (LoC) devices, optics, biomedical applications, and electronic paper (e-paper). Generally, Young-Lippmann (Y-L) equation is used to relate the mechanical and electrical force involved in electrowetting-on-dielectric (EWOD) based actuation. And the general trend is to neglect the effect of double layer capacitance formed at the metal-liquid interface considering the Debye-length to be in the order of nanometer. But, at electrode-electrolyte-insulator interface, the effect of interface layer capacitance becomes significant and often leads to the mismatch between the experimental observation and theoretical result. In this work, the surface behaviour of polydimethylsiloxane (PDMS) for EWOD application is studied experimentally and a term "k " has been introduced in the Y-L equation to match the theoretical and experimental result. Effect of interface layer capacitance has been observed in contact angle versus applied voltage experiment with different pH buffer solution. The introduction of "k " term takes care of the interface layer capacitance which can not be neglected and plays a vital role when the applied electric potential is high.